Large-Format Additive Manufacturing and Machining Using High-Melt-Temperature Polymers. Part II: Characterization of Particles and Gases - Stefaniak, Aleksandr B; Bowers, Lauren N; Martin, Jr, Stephen B; Hammond, Duane R; Ham, Jason E; Wells, J R; Fortner, Alyson R; Knepp, Alycia K; du Preez, Sonette; Pretty, Jack R; Roberts, Jennifer L; du Plessis, Johan L; et al. (ACS Chemical Health & Safety., 2021)
Extrusion of high-melt-temperature polymers on large-format additive manufacturing (LFAM) machines releases particles and gases, though there is no data describing their physical and chemical characteristics. Emissions from two LFAM machines were monitored during extrusion of acrylonitrile butadiene styrene (ABS) and polycarbonate (PC) polymers as well as high-melt-temperature Ultem (poly(ether imide)), polysulfone (PSU), poly(ether sulfone) (PESU), and polyphenylene sulfide (PPS) polymers. Filter samples of particles were collected for quantification of elements and bisphenol A and S (BPA, BPS) and visualization of morphology. Individual gases were quantified on substance-specific media. Aerosol sampling demonstrated that concentrations of elements were generally low for all polymers, with a maximum of 1.6 mg/m for iron during extrusion of Ultem. BPA, an endocrine disruptor, was released into air during extrusion of PC (range: 0.4 ± 0.1 to 21.3 ± 5.3 g/m ). BPA and BPS (also an endocrine disruptor) were released into air during extrusion of PESU (BPA, 2.0-8.7 g/m ; BPS, 0.03-0.07 g/m ). Work surfaces and printed parts were contaminated with BPA (<8-587 ng/100 cm ) and BPS (<0.22-2.5 ng/100 cm ). Gas-phase sampling quantified low levels of respiratory irritants (phenol, SO , toluene, xylenes), possible or known asthmagens (caprolactam, methyl methacrylate, 4-oxopentanal, styrene), and possible occupational carcinogens (benzene, formaldehyde, acetaldehyde) in air. Characteristics of particles and gases released by high-melt-temperature polymers during LFAM varied, which indicated the need for polymer-specific exposure and risk assessments. The presence of BPA and BPS on surfaces revealed a previously unrecognized source of dermal exposure for additive manufacturing workers using PC and PESU polymers.